2014
DOI: 10.1186/s13058-014-0415-9
|View full text |Cite
|
Sign up to set email alerts
|

A joint analysis of metabolomics and genetics of breast cancer

Abstract: IntroductionRemodeling of cellular metabolism appears to be a consequence and possibly a cause of oncogenic transformation in human cancers. Specific aspects of altered tumor metabolism may be amenable to therapeutic intervention and could be coordinated with other targeted therapies. In breast cancer, the genetic landscape has been defined most comprehensively in efforts such as The Cancer Genome Atlas (TCGA). However, little is known about how alterations of tumor metabolism correlate with this landscape.Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
160
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 175 publications
(180 citation statements)
references
References 54 publications
(57 reference statements)
18
160
0
Order By: Relevance
“…Additional information for the experiments with [1][2][3][4][5][6][7][8][9][10][11][12][13] C]glutamine can be found in the Supplemental Methods. To determine the flux of [ 13 C]glutamine into succinate and citrate in presence and absence of cell-permeant 2HG, MCF12A cells were seeded in a 6-well plate and serum-starved overnight before being exposed to either 1 mM octyl-2HG or control compound (PAMO) in RPMI medium containing 2 mM [1-5 13 C]glutamine (Cambridge Isotope Laboratories).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Additional information for the experiments with [1][2][3][4][5][6][7][8][9][10][11][12][13] C]glutamine can be found in the Supplemental Methods. To determine the flux of [ 13 C]glutamine into succinate and citrate in presence and absence of cell-permeant 2HG, MCF12A cells were seeded in a 6-well plate and serum-starved overnight before being exposed to either 1 mM octyl-2HG or control compound (PAMO) in RPMI medium containing 2 mM [1-5 13 C]glutamine (Cambridge Isotope Laboratories).…”
Section: Methodsmentioning
confidence: 99%
“…We and others previously reported that total 2HG accumulates in a subset of human breast tumors that were primarily estrogen receptor-negative (ER-negative) (7,8). Here, we interrogated the enantiomeric forms of 2HG in 15 ER-negative human breast tumors using enantiomer-specific targeted mass spectrometry ( Figure 1A).…”
Section: D-2hg Is the Predominant Enantiomer Elevated In Human Breastmentioning
confidence: 99%
See 2 more Smart Citations
“…Individuals with ERα positive (ERα+) breast cancer as determined by immunohistochemistry (IHC), accounts for approximately 70% of breast cancer patients. Comparative metabolomics profiling of ERα+ and ERα negative (ERα-) breast cancer indicated clear metabolic differences correlated to hormone receptor status, including differences in glutamine and beta-alanine metabolism, as well as phospholipid metabolism (9)(10)(11). Furthermore, estrogen stimulation enhanced the rate of glucose consumption, lactate production (aerobic glycolysis), and glutamate synthesis, and decreased the level of phosphocholine (PCho) in breast cancer cell lines (12-14).…”
Section: Introductionmentioning
confidence: 99%